Development of Problem-Based Learning–Based Student Worksheets Integrated With Catur Pramana To Improve Elementary School Students’ Science Process Skills - Ni Wayan Sri Darmayanti; Putu Beny Pradnyana; Desak Putu Anom Janawati; Putra I.P.A.S; Devi N.K.J.S. (Cakrawala: Jurnal Pendidikan, 2026)
This study aims to develop Student Worksheets (LKPD) by integrating the Problem-Based Learning (PBL) model with Catur Pramana values. Utilizing the ADDIE framework, the research produced a science learning instrument tailored for elementary education. Expert validation confirmed the quality of the product with an Aiken’s V index of 0.77, indicating high validity. Furthermore, the effectiveness test revealed a significant enhancement in student performance, with average scores rising from 15.6 (pre-test) to 25.4 (post-test). With an N-gain score of 0.7 and an effectiveness rate of 68%, the developed LKPD is categorized as moderately effective and serves as a strategic tool for fostering students' science process skills..